Hubungan tingkat pengetahuan ibu mengenai pemenuhan gizi 1000 hari pertama kehidupan dengan kejadian underweight - Fitry Ramdani; Muhammad Noris; Dea Zara Avila; Muammar Iksan (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Being underweight is a key indicator reflecting the combined impact of acute and chronic malnutrition. Although various countries have implemented nutrition interventions, progress remains insufficient to ensure the achievement of all global nutrition targets by 2030. Findings from the 2025 Joint Child Malnutrition Estimates (JME) highlight the need for intensified efforts to prevent and address child malnutrition, including underweight status, by improving access to nutritious food and quality healthcare services, as well as promoting optimal child-feeding practices. Purpose: To analyze the relationship between maternal knowledge regarding the